Exploring Speech Act of English and Tshivenda Representatives and Directives - Nephawe, Farisani Thomas; Lambani, Matodzi Nancy (Technium Social Sciences Journal, 2021)
Competence in English pragmatics enhances the use of English in social contexts throughout the world. However, using English as a second language is always problematic particularly when it comes to the interpretation of speech act in English. The differences in structure and function between English and other languages such as Tshivenda are conspicuous. The current research explored Speech Act of English and Tshivenda representatives and directives among the Tshivenda-speaking people. The findings revealed that the Tshivenda-speaking people faced difficulties utilising English Speech Acts such as representatives, and directives. The research recommends frequent interaction between those proficient in English and Tshivenda-speaking people.